Gregory the Great : A Symposium - Cavadini John C. (Book collections on Project MUSE., 1995)
"A group of renowned North American scholars gathered at the University of Notre Dame in 1993 for a symposium on Pope Gregory the Great (550-604). The essays collected in this volume are arranged in the order in which they were delivered, and several additional contributions are included as well."--Jacket